2021
DOI: 10.1186/s40352-021-00149-3
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen years of manifestations and factors of health insurance fraud, 2006–2020: a scoping review

Abstract: Background Healthcare fraud entails great financial and human losses; however, there is no consensus regarding its definition, nor is there an inventory of its manifestations and factors. The objective is to identify the definition, manifestations and factors that influence health insurance fraud (HIF). Methods A scoping review on health insurance fraud published between 2006 and 2020 was conducted in ACM, EconPapers, PubMed, ScienceDirect, Scopus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Among the key findings of our study, the most important contributing factors to health insurance fraud are policy type, education, and claimant age. Like our findings, Villegas-Ortega et al identified macroenvironmental factors (culture, regulations); mesoenvironmental factors (provider characteristics, management policy, reputation); microenvironmental factors (sex, race, insurance condition, language, treatments, future risk of disease); and other factors that influence health insurance fraud (Villegas-Ortega et al 2021). Regarding policy type, claimants with VIP (comprehensive-coverage policy) were associated with more fraudulent acts.…”
Section: Discussionsupporting
confidence: 80%
“…Among the key findings of our study, the most important contributing factors to health insurance fraud are policy type, education, and claimant age. Like our findings, Villegas-Ortega et al identified macroenvironmental factors (culture, regulations); mesoenvironmental factors (provider characteristics, management policy, reputation); microenvironmental factors (sex, race, insurance condition, language, treatments, future risk of disease); and other factors that influence health insurance fraud (Villegas-Ortega et al 2021). Regarding policy type, claimants with VIP (comprehensive-coverage policy) were associated with more fraudulent acts.…”
Section: Discussionsupporting
confidence: 80%
“…More details about the characteristics of the included studies are shown in Appendix 2. The included studies utilized AI for fraud detection (n=17) [1,2,6,8,14,17,18,19,21,22,23,24,26,27,28,30,31], identifying and classifying detected fraud (n=8) [3,4,11,12,13,15,20,25], and investigating and analyzing fraudulent data (n=6) [5,7,9,10,16,29]. The most common algorithm used in the included studies was Convolutional Neural Network (CNN) (n=13), followed by Artificial Neural Network (ANN) (n=10).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that health insurance fraud leads to a significant increase in the cost of national health insurance programs and is one of the main causes of inefficiencies in the operation of health insurance funds [4,5]. In particular, in some high-income countries, 3-10% of annual healthcare expenditures are lost as a result of health insurance fraud, amounting to billions of dollars [6][7][8][9]. However, due to the unique characteristics of the health insurance industry and the complex and insidious of health insurance fraud, the supervision of health insurance funds is very difficult [10,11].…”
Section: Introductionmentioning
confidence: 99%